Multi‐stage metamorphism by progressive accretion of continental blocks, example from the Western Hindu Kush. (30th June 2020) - Moiny, Hezbullah; Faryad, Shah Wali; Čopjaková, Renata; Jedlicka, Radim
Abstract: Basement rocks from the Western Hindu Kush preserve evidence of multiple metamorphic and magmatic events that occurred along the boundary between the Archean–Proterozoic Afghan Central and Afghan–Tajik Blocks. To verify the different metamorphic stages or events, mineral textures and phase equilibria in metamorphic basement rocks and their age relations to magmatic episodes have been investigated. Quartzofeldspathic gneiss and migmatite with lenses of amphibolite (with assumed Proterozoic age for their metamorphism) are intruded by the Triassic Hindu Kush granitoid batholith and small Cretaceous and Oligocene granite intrusions. The age of thermal overprint (210–170 Ma) by the Triassic batholith is confirmed by new monazite data. Both Triassic and Cretaceous granitoids and surrounding basement rocks underwent subsequent metamorphism up to epidote–amphibolite facies. The degree of this metamorphism increases southward at the contact to the Kabul Block, which under‐plates the Western Hindu Kush from the south. An early Miocene age was obtained by Pb–Th analyses in thorite and huttonite, which are close or slightly younger than the Oligocene granite in this area. The Cretaceous meta‐granodiorite near the border with the Kabul Block contains xenoliths of granulite facies rocks that could come from the Neoarchean granulite facies basement of the Kabul Block. The multi‐stage metamorphic and magmatic evolution classifies the Hindu Kush mountain belt as a long‐lived suture zone that was active since the early Palaeozoic. The results of this study support the interpretation about possible relations of the Afghan Central Blocks to the southern margin of Eurasia during the evolution of Para‐ and Neotethys.